Local Government Strategy in Improving the Quality and Capabilities of Civil Servants in the Digital Era (Universitas Terbuka, 2023)
The digitalization era demands local governments to be resilient and prepared to face various challenges. Improving the quality of public services becomes a necessity to meet the needs of the community. The competence of civil servants should be continuously enhanced, enabling them to adapt to the changing times. This paper aims to examine the strategies employed by the local government to enhance the quality and competence of civil servants in addressing challenges in the digital era. The research location is Wonosobo Regency, Central Java Province. A qualitative descriptive research method is utilized, involving data collection through interviews, analysis of news from the Wonosobo government website, and literature review on similar studies. The research findings indicate the necessity of specialized training for civil servants to improve their quality and competence, considering the unavoidable progress of the digital era. The Wonosobo government has implemented the Government Transformation Academy (GTA) as a training facility for civil servants to enhance their quality and competence in the current digital era. The program aims to equip civil servants in Wonosobo Regency with the skills to effectively utilize technology and information in fulfilling organizational duties and providing excellent services.